An Analysis of the Government Financial Performance Influence on Community Welfare in North Sulawesi Province Indonesia - Mangantar, Maryam (International Journal of Economics and Financial Issues, 2018)
This study aims to analyze the influence of local financial independence on the welfare of the community and analyze the effect of regional income growth on the welfare of the community. Samples were taken by census from all District and Municipal Government Financial Statements throughout North Sulawesi Province. Hypothesis testing is done by linear regression analysis and the results of research indicate that the regional financial independence affects people's welfare and income. Similarly, local revenue affects the level of people's welfare in North Sulawesi. Keywords: financial performance, community welfare, north Sulawesi province JEL Classifications: E62, D6 DOI: https://doi.org/10.32479/ijefi.6949